Two relish isoforms produced by alternative splicing participate in the regulation of antimicrobial peptides expression in Procambarus clarkii intestine. Issue 99 (April 2020) - Zhang, Zhuoxing; Zhang, Chao; Dai, Xiaoling; Zhang, Ruidong; Cao, Xueying; Wang, Kaiqiang; Huang, Xin; Ren, Qian
Abstract: Nuclear factor κB (NF-κB) plays a key role in the innate immunity of invertebrates. Relish belongs to the NF-κB family. In insects, alternative splicing induces the sequence diversity of the Relish gene. However, information on the roles of various relish isoforms in crustacean innate immune response is limited. Here, two alternatively spliced Relish isoforms (designated as SPcRelish and LPcRelish ) were identified from freshwater crayfish ( Procambarus clarkii ), and functional analysis was performed. The Relish gene has 25 exons and 24 introns. The long isoform LPcRelish is fully spliced, whereas the short isoform SPcRelish is alternatively spliced and contains exon 1–9 and a retention of intron 9. LPcRelish contains the Rel homology domain (RHD), the ig-like, plexins, transcription factors (IPT), and ankyrin-repeat (ANK) inhibitory domain. However, SPcRelish contains only the RHD and IPT domain, and does not have an ANK domain. The transcripts of SPcRelish and LPcRelish can be regulated by Vibrio parahaemolyticus . The intestinal immunological barrier and bacterial balance in the intestine play crucial roles in host health. In this study, we analyzed the connection between Relish isoforms and the transcripts of antimicrobial peptides (AMPs) in intestine. The transcripts of all the tested AMPs, except ALF -41125, were upregulated by V. parahaemolyticus . The knock down of the SPcRelish gene resulted in a significant decrease in the expression levels of ALF -7032, ALF -13162, and Crustin -42012 during V. parahaemolyticus invasion. The expression levels of four AMP genes ( ALF -41125, ALF -42430, Crustin -41354, and Crustin -42993) were obviously increased in V. parahaemolyticus -challenged SPcRelish -silenced crayfish. ALF -7032, ALF -9228, ALF -13162, ALF -42430, Crustin -41354, Crustin -42012, and Crustin -42993 were evidently downregulated in V. parahaemolyticus -infected LPcRelish -silenced crayfish. Overall, generating the two Relish isoforms by alternative splicing may be an important mechanism of the host immune system to promote molecular diversity, which results in the functional diversity of the relish transcription factor. Highlights: Two relish isoforms produced by alternative splicing were identified from Procambarus clarkii. LPcRelish is fully spliced, while SPcRelish is alternative spliced with intron retention. The expression of LPcRelish, SPcRelish, and seven AMPs were regulated by Vibrio parahaemolyticus challenge. LPcRelish and SPcRelish show functional diversity in activating the AMP genes during Vibrio infection.